2022
DOI: 10.1155/2022/6796160
|View full text |Cite
|
Sign up to set email alerts
|

New Path of Stranger Interaction Platform and Network Cross-Cultural Communication in the Omnimedia Era

Abstract: The Internet is a new medium for disseminating information. The emergence of online information dissemination tools has overcome the limitations of time and space in the early information dissemination tools, and online information dissemination has extraordinary attractiveness in all walks of life. Online communication is the dissemination of information, including news, knowledge, and other information, through computer networks. The benefits of high speed, high volume, interactivity, immediacy, vividness, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In developed countries such as the United States and the United Kingdom, traditional publishing institutions still occupy the main position of national publishing business, and the online publishing industry and creative mechanism are relatively backward compared to China, making it difficult to meet the reading needs of foreign readers [5]. In recent years, with the continuous acceleration of globalization, exchanges between different ethnic groups and cultures have become more frequent and extensive, greatly increasing the level of cultural acceptance among different countries and ethnic groups [6,7].…”
Section: Development Status Of International Communication Of Chinese...mentioning
confidence: 99%
“…In developed countries such as the United States and the United Kingdom, traditional publishing institutions still occupy the main position of national publishing business, and the online publishing industry and creative mechanism are relatively backward compared to China, making it difficult to meet the reading needs of foreign readers [5]. In recent years, with the continuous acceleration of globalization, exchanges between different ethnic groups and cultures have become more frequent and extensive, greatly increasing the level of cultural acceptance among different countries and ethnic groups [6,7].…”
Section: Development Status Of International Communication Of Chinese...mentioning
confidence: 99%
“…Alongside the non-stop technological advancement, culture interconnection, and language exploration via different interfaces, a powerful tool called Virtual Reality (VR) has been generated. global citizenship, educators can facilitate cross-cultural discussions and exchanges, and prepare students for a globalized world" (Edgar, 2023, p. 14) Likewise, Li (2022) concluded that technology can enhance language development and promote an encouraging environment for language learners by applying cross-cultural communication and intercultural understanding. The authors examined the immense impact of technology on the development of language skills through cross-cultural communication in the higher educational context.…”
Section: Introductionmentioning
confidence: 99%